Effects of Marinating Factors on the Quality of Beef Satay - Cheok, Choon Yoong (2009)
A series of experiments were undertaken to investigate the effects of satay marinade on beef texture by measuring its physical changes in terms of weight gain, cooking loss and WBSF values. Experiment I was designed to find the main substances in satay marinade that alters the weight gain, cooking loss and WBSF values. Tenderloin beef muscle was selected and assigned into five treatments; i.e., control, brine solution, tamarind juice, tamarind juice plus salt and satay marinade for 30, 60, 90, 120, 150, and 180 minutes of marinating time. Experiment II was conducted to investigate the influence of muscles type, blade roast (BR), biceps femoris (BF) and semitendinosus (ST) on weight gain and cooking loss, and the semitendinosus muscle was used for further assessment of tenderness. All the beef muscles were assigned into treatments and marinating times as defined in experiment I. Experiment III was designed to find the better marinating temperature between 4 °C (in refrigerator) and 25 °C (room temperature) on weight gain for beef cuts in satay marinade Chuck tender beef cuts were assigned into two treatments of control and satay marinade in two different marinating temperatures of 4 °C and 25 °C for 1st, 2nd, 3rd, 4th, 5th and 6th hour of marinating times. The marinating time was extended to 7th, 9th, 12th and 24th hour for the 4°C in order to establish a relationship between weight gain and marinating time. Experiment IV was conducted to find the correlation between weight gain, cooking loss and WBSF values of tenderloin beef cuts marinated in satay marinade for 1, 2, 3, 4, 5, and 6 hours marinating time at 4°C. Tenderloin beef cuts that were marinated in tamarind juice plus salt and satay marinade did not show significant difference (P > 0.01) in weight gain, cooking loss and WBSF which implied that tamarind juice plus salt were the main substances in satay marinade which attributed to changes in measured physical parameters. Although the tamarind juice provided the acidic condition to the marinades, it did not enhance meat water effectively due to the inductive effect of tartaric acid. Linear regression analysis found that the tenderness of tenderloin samples increases linearly (P < 0.05) with increasing weight gain, but it decreases linearly (P < 0.05) with increasing cooking loss, irrespective of treatments. The weight gain of both BF and ST were found significantly higher (P < 0.01) than BR, but showed no significant difference (P > 0.01) between themselves in brine solution, tamarind juice plus salt and satay marinade treatments, which implied that BF and ST muscles from the same carcass have almost similar water binding ability. The beef chuck cuts marinated in satay marinade at 4 °C is more flavourable in meat water enhancing compared to 25 °C (P < 0.01), but the influence of marinating temperature will only be significance for at least two hours of marinating time. A best fitted equation was established to express the relationship of weight gain of beef cuts marinated at 4 °C in response to marinating time up to 24th hour. Prediction from the equation found that the extended marinating time above six hours did not give any significant positive effect in water enhancing for beef chuck muscles marinated in satay marinade at 4 °C, and the weight gain rate was found at highest rate at the first two hours of marination, particularly at the beginning of 10 minutes. The strong negative correlation between weight gain and WBSF (P < 0.05), and positive correlation between cooking loss and WBSF values (P < 0.01) found for tenderloin meat marinated in satay marinade highlighted the importance of water enhancement and cooking loss reduction in determining the tenderness of cooked tenderloin cuts. The local tenderloin beef and chuck tender block were recommended in preparation of satay based on data obtained. Marinating time of two hours at 4 °C is sufficient for beef cuts to equilibrate with satay marinade in order to have maximum water enhanced